Effectiveness of a nursing innovation workshop at enhancing nurses' innovation abilities: A quasi‐experimental study - Limei Gao; Qiaocong Lu; Xiangchuan Hou; Jiefen Ou; Mingzhu Wang (Wiley, 2022)
Abstract Aim To investigate the effectiveness of nursing innovation workshop in enhancing clinical nurses' innovation ability and research ability in a tertiary hospital. Design A quasi‐experimental study design. Methods Thirty‐seven recruited nurses participated in a nursing innovation workshop for half a year in a tertiary hospital in Guangdong between June 2019 and March 2020. Questionnaire data on the nurses' self‐rated innovation and research abilities were collected before the training and 3 months after completing the training. Wilcoxon signed rank tests were used to analyse differences within the group before and after the intervention. The level for statistical significance was set at p ≤ .05 (two‐tailed). Results Nurses' self‐rated innovation ability (p < .001, 95% confidence interval 12.79 to 15.05) and research ability (p < .001, 95% confidence interval 14.39 to 19.09) improved significantly after the training. Since the whole design lacked a control group, the study needs to be further verified in more hospitals and among more nurses.